(untitled) (Nordic Journal of African Studies, 2002)
The aim of this study was to find out whether our observations that secondary school students made more mistakes when they used the hq nominal group (NG) structures than when they used any other structure including the mhq is scientifically verifiable. The data used for the study were written English compositions by 250 students randomly selected from five secondary schools in the Ede Zone of Osun State. Having analysed their written tasks, it was found that the hq type, which is structurally less complex than the mhq type, was more difficult to acquire. The study therefore recommended that the mhq type of NG should be taught before the hq type as the hq type did not have to be acquired before the mhq type.